2009
DOI: 10.1002/ijc.24397
|View full text |Cite
|
Sign up to set email alerts
|

A novel anticancer effect of Astragalus saponins: Transcriptional activation of NSAID‐activated gene

Abstract: Astragalus membranaceus has been used to ameliorate the side effects of antineoplastic drugs because of its immunomodulating nature. We had recently demonstrated that total Astragalus saponins (AST) possess anticarcinogenic and proapoptotic properties in human colon cancer cells and tumor xenograft. In this study, we identified NSAID-activated gene (NAG-1) as a potential molecular target of AST. The growth-inhibitory and proapoptotic effects of AST were assessed in a panel of human cancer cell lines. Hoechst 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…Anticancer agents derived from botanical herbs such as camptothecin and paclitaxel are the drugs of first choice in many tumor therapies, accounting for more than 30% of all anticancer drugs (9,10). Many scholars in China have come to believe that it is important to screen antitumor active ingredients from botanical herbs, particularly from traditional Chinese medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer agents derived from botanical herbs such as camptothecin and paclitaxel are the drugs of first choice in many tumor therapies, accounting for more than 30% of all anticancer drugs (9,10). Many scholars in China have come to believe that it is important to screen antitumor active ingredients from botanical herbs, particularly from traditional Chinese medicines.…”
Section: Introductionmentioning
confidence: 99%
“…62 In addition, particular saponins induce GDF-15 in a PI3K-dependent manner. 63 Further evidence that GDF-15 has a role in cellular stress responses was presented in the work of Schlittenhardt et al, which showed enhanced expression of GDF-15 induced by oxidized low-density lipoproteins, TNFa, certain ceramides or hydrogen peroxide. This group also demonstrated the immunohistochemical colocalization of GDF-15 with PARP, caspase-3, manganese, super-oxide dismutase, cJun and p53 in native atherosclerotic tissue.…”
Section: Regulation Of Gdf-15 Expressionmentioning
confidence: 97%
“…[1], is one of the most widely used traditional Chinese medicine in China and other Oriental countries. It possesses various biological activities including immune-modulation [2,3], cardioprotective [4], anti-oxidative [5], anti-tumor [6] and antiinflammatory [7]. Chemical and biological investigations on Radix Astragali have revealed that triterpene saponins, flavonoids and polysaccharides are the main active components [2,6,8].…”
Section: Introductionmentioning
confidence: 99%